Comparative Infectivity of Papaya Ringspot Virus (PRSV) Subjected to Mutagens and Heat Attenuation in Carica papaya L. (Solo Variety) - Teves, Franco (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Putative mild strains of the papaya ringspot virus (PRSV) were generated using nitrous acid treatment and heat attenuation based on cross-protection experiments on papaya seedlings. Ultraviolet light irradiation of the severe strain of the virus did not reduce its virulence as shown by the apparent absence of cross protective capability. The pflesence of P RSV in papaya seedlings showing either no or mild symptoms after the cross-protection experiment was determined serologically using enzyme-linked immunosorbent assay (ELISA). This result is significant in that these locally-generated putative mild P RSV strains showed cross-protective properties on experimental papaya seedlings. The application of cross-protection technology along with the cultivation of tolerant or resistant papaya varieties would be the only means by which plantations in Mindanao can withstand the devastating effects of this virus already felt in the Visayas after successfully spreading from Luzon.